2002
DOI: 10.1128/jb.184.14.3801-3807.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from Terminal Recombination Gradients that FtsK Uses Replichore Polarity To Control Chromosome Terminus Positioning at Division inEscherichia coli

Abstract: Chromosome dimers in Escherichia coli are resolved at the dif locus by two recombinases, XerC and XerD, and the septum-anchored FtsK protein. Chromosome dimer resolution (CDR) is subject to strong spatiotemporal control: it takes place at the time of cell division, and it requires the dif resolution site to be located at the junction between the two polarized chromosome arms or replichores. Failure of CDR results in trapping of DNA by the septum and RecABCD recombination (terminal recombination). We had propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 34 publications
4
72
0
Order By: Relevance
“…Our prior study implies that recurring DNA sequences regulate the direction of FtsK translocation (5). These results substantiate genetic evidence that the misorientation of polar sequences near dif, such as lambda insertions, can disrupt proper segregation of the terminus region (11,12). The polarity of a sequence can be quantified as a skew, which is defined as the percentage of occurrences of the sequence on the leading strand.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Our prior study implies that recurring DNA sequences regulate the direction of FtsK translocation (5). These results substantiate genetic evidence that the misorientation of polar sequences near dif, such as lambda insertions, can disrupt proper segregation of the terminus region (11,12). The polarity of a sequence can be quantified as a skew, which is defined as the percentage of occurrences of the sequence on the leading strand.…”
supporting
confidence: 57%
“…1 A). One of the major reasons that RAG was proposed as an FRS is its very high skew of 97 (P ϭ 2.9 ϫ 10 Ϫ17 ) at 100 kb and 88 (P ϭ 1.9 ϫ 10 Ϫ97 ) at 1 Mb from dif (12). However, as we show below, such a high skew is not necessary to impart directionality.…”
Section: Identification Of Ftsk Turnaroundmentioning
confidence: 75%
See 2 more Smart Citations
“…A recent single molecule study, however, demonstrated that the sequence of the terminus region is the sole determinant necessary for guiding the protein towards the dif site [Pease et al, 2005]. Directional information could be provided by short repeated sequences identified in the terminal part of the chromosome [Corre and Louarn, 2002], the orientation of which is biased and abruptly changes at dif, thereby pointing toward the site of dimer resolution [Salzberg et al, 1998]. …”
Section: The Last Stages Of Dna Replicationmentioning
confidence: 99%